Factors associated with Immunisation coverage in children of migrant brick kiln workers in selected districts of Bihar, India - Kumar, Pragya; Ranjan, Alok; Kumar, Dhananjay; Pandey, Sanjay; Singh, C M; Agarwal, Neeraj (Indian Journal of Community Health, 2020)
Background: Brick kiln workers are unskilled labourers and keep migrating from one place to another leading to non/partial immunization of their children. The study was conducted to estimate the prevalence of full immunisation among the children of mother living in brick kiln and to assess the factors associated with incomplete or non-immunisation. Methods: The study was conducted using stratified cluster sampling technique in different brick kilns of four districts of Bihar. Results: Out of 332 children the prevalence of full immunization was 55.43% and partial immunization was 37.65% while 6.92 % children were not immunized at all. The most common reason for non/partial immunization was lack of awareness about importance of immunization (37.2%) followed by no information of nearest place of vaccination (33.1%). Conclusion: The routine immunization coverage has increased but it is still low among migrant brick kiln workers.